Use of termitarium soil as a viable source for biofertilizer and biocontrol - Adebajo, Seun Owolabi (2023)
Twenty-seven soil samples were collected from nine different mound soil (household, farm and water bodies in a sterile sample bag). Aliquots of serially diluted samples were plated on nutrient agar, plate count agar, eosin methylene blue agar and MacConkey agar plates. Isolates were identified using standard microbiological techniques. Identified isolates were screened for plant growth-promoting properties using phosphate solubilization test, potassium solubilization test and indole acetic acid production test. Activities of the plant growth-promoting bacteria were carried out using antagonism by diffusible substance method and antagonistic activity of cell-free culture filtrate of bacterial isolates against Ralstonia solanacearum and Fusarium oxysporum. Two hundred bacterial isolates were recovered from the 27 soil samples. The most predominant isolate was Bacillus spp. Out of the 200 bacterial isolates, 57 were positive for phosphate solubilization test, potassium solubilization test and indole acetic acid production test. Out of the 57 isolates, six bacterial isolates had antagonistic activities against Fusarium oxysporum, while seven bacterial isolates antagonized Ralstonia solanacearum.